Correlation between Breastfeeding Duration and Motor Development in Children - Siregar, Gurnal Rai Gandra; Lubis, Munar; Fujiati, Isti Ilmiati (Talenta Publisher, 2018)
World Health Organization (WHO) recommends to continue breastfeeding until two years of age. There are few studies assessing the correlation between breastfeeding duration and motor development. A cross-sectional study was conducted in April 2016 in Muara Batang Gadis District. The sample were children 3-6 years of age. Breastfeeding duration was obtained by interview, and motor development was assessed using Denver Developmental Screening Test II. Chi-square test was used to evaluate the correlation between breastfeeding duration and motor development, with P-value <0.05 and 95% Confidence Interval (CI). Among 204 children, 5.4% had the fine motor delay, and 1% had the gross motor delay. Children with breastfeeding duration for at least for two years had better fine motor development compared to breastfeeding duration for less than two years (P<0.001, PR=1.139, 95% CI=1.055-1.231) and there is no difference in gross motor development (P=0.193, PR=1.023, 95% CI=0.991-1.055). There is a correlation between breastfeeding duration and fine motor development.